2000 Families Research: Some Findings and Potential for Future Research - Ayşe Güveli (Journal of Economy Culture and Society)
We have only a limited understanding of the consequences of migration for migrants and their descendants, relative to staying behind; and our insights of intergenerational transmission is limited to two generations of those living in the destination countries. These limitations stem from a scarcity of studies and data that include comparisons with those left behind and return migrants – in origin countries and which trace processes of intergenerational transmission over multiple generations in the migration context. This paper outlines the theoretical and methodological discussions in the field and data of the 2000 Families study. It introduces the unique design of the 2000 Families study, and its datasets, and discusses the research potential for future research. This study provides some core findings from the study, framed within a theoretical perspective of “dissimilation from origins”, and reflects on its potential for future migration research in all fields of the social sciences. The rich datasets are stored in the GESIS data archive and are open for researchers to explore and answer hitherto unanswerable research questions on multigenerational transmission, international migration, Turkish migration, (transnational) family relations, friendship, socioeconomic, cultural, political, religious behaviour, attitudes, values and relations.